2015
DOI: 10.1098/rspb.2014.2384
|View full text |Cite
|
Sign up to set email alerts
|

The forest or the trees: preference for global over local image processing is reversed by prior experience in honeybees

Abstract: Traditional models of insect vision have assumed that insects are only capable of low-level analysis of local cues and are incapable of global, holistic perception. However, recent studies on honeybee (Apis mellifera) vision have refuted this view by showing that this insect also processes complex visual information by using spatial configurations or relational rules. In the light of these findings, we asked whether bees prioritize global configurations or local cues by setting these two levels of image analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 100 publications
(158 reference statements)
1
64
0
Order By: Relevance
“…In these experiments, they do learn to make the selective discriminations required from both tasks [26]. Prior learning experience can also modify bees' natural preference for global information and lead to them selectively attending to local information over global features in a stimulus [71]. These examples seem to make a clear case for learning and memory influencing a bee's visual search behaviour during foraging tasks.…”
Section: Top-down Sensitivity Controlmentioning
confidence: 99%
“…In these experiments, they do learn to make the selective discriminations required from both tasks [26]. Prior learning experience can also modify bees' natural preference for global information and lead to them selectively attending to local information over global features in a stimulus [71]. These examples seem to make a clear case for learning and memory influencing a bee's visual search behaviour during foraging tasks.…”
Section: Top-down Sensitivity Controlmentioning
confidence: 99%
“…For example, bees may need to memorize complex flower patterns to avoid deceptive plant flowers (Stejskal, Streinzer, Dyer, Paulus, & Spaethe, 2015). Interestingly, it has also been demonstrated that honeybees have the capacity to rely on configural processing with prolonged visual experience (Avarguès-Weber, Portelli, et al, 2010;Stach, Benard, & Giurfa, 2004;Stach & Giurfa, 2005), thus offering a fascinating parallel with primate visual processing (Avarguès-Weber et al, 2015).…”
mentioning
confidence: 99%
“…In parallel, the honeybee has emerged as a major model of visual cognitive processing in insects (Avarguès-Weber, Deisig, & Giurfa, 2011;Avarguès-Weber, Dyer, Combe, & Giurfa, 2012;Avarguès-Weber, Dyer, Ferrah, & Giurfa, 2015;Avarguès-Weber & Giurfa, 2013;Chittka & Niven, 2009;Howard, Avarguès-Weber, Garcia, & Dyer, 2017;Srinivasan, 2010). The honeybee can be trained to solve perceptually or cognitively difficult visual tasks in free-flying conditions by collecting sucrose associated with a target visual stimulus while an alternative stimulus offers a distasteful substance (quinine; Avarguès-Weber, de Brito Sanchez, et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bees have a trichromatic (UV-, blue-, green-sensitive) visual system, allowing fine colour (Avargues-Weber et al, 2010;Dyer et al, 2011;Peitsch et al, 1992) and spatial (Avargues-Weber et al, 2015;Giurfa et al, 1999) discrimination. Bees also possess a capacity to accurately sense olfactory cues (Giurfa and Sandoz, 2012), and a capacity to perceive tactile cues on flowers via mechano-receptive sensilla trichodea (Erber et al, 1998;Kevan and Lane, 1985).…”
Section: Introductionmentioning
confidence: 99%